Calidad de cuidado de enfermería al paciente hospitalizado y nivel de satisfacción del familiar, servicio de emergencia de HVLE. Trujillo, 2015 - García Vega, Sandra (2016)
This research study, quantitative, descriptive, correlational, was performed at the Hospital Victor Lazarte Echegaray in the Province of Trujillo - 2015, in order to determine the relationship between the quality of nursing care and inpatient level family satisfaction. The sample consisted of 70 adults hospitalized patients and 70 relatives, 18 to 60, emergency service Hospital Víctor Lazarte Echegaray that met the inclusion criteria of the investigation. The survey on the perceived quality of nursing care for the hospitalized patient and Satisfaction Survey Family: two instruments used for data collection. The information obtained was processed and analyzed by statistical test "Chi square". He reached the following conclusions: 1) the total of hospitalized adult patients, aged 18 to 60 years, 60 percent have good quality nursing care; 31 percent have regular quality of nursing care; while 9 percent have bad quality of nursing care. Hospital Víctor Lazarte Echegaray emergency service. Trujillo, 2015. 2) The 57 percent of families, 18 to 60, have a good level of satisfaction; 29 percent satisfaction level regularly; while the other 14 percent have deficient level of satisfaction. Hospital Víctor Lazarte Echegaray emergency service. Trujillo, 2015. 3) The quality of nursing care of hospitalized adult patients keeps highly significant statistical relationship with their level of satisfaction of the family (p = 0.001). Hospital Víctor Lazarte Echegaray emergency service. Trujillo, 2015.